2021
DOI: 10.18393/ejss.829695
|View full text |Cite
|
Sign up to set email alerts
|

Some soil biological and chemical properties as affected by biofertilizers and organic ameliorants application on paddy rice

Abstract: Biofertilizers are compounds that contain microorganisms capable of increasing the nutrient availability to plants and increasing plant growth rate. The purpose of this research is to study the effects of biofertilizers and organic ameliorants on some of soil bio-chemical properties. The pot experiment was conducted at the field of the Faculty of Agriculture, Universitas Padjadjaran Indonesia. The experiment was conducted in a randomized block complete design format consisting of twelve treatments and three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…The pH and EC of soil were reported to be negatively affected by the microbial population of jeevamrut and soil. The experimental findings confirm that the application of jeevamrut and biofertilizers have increase the humification and mineralization of organic matter present in the soil to release the nutrients [12,16]. Further, the acidic medium developed during the decomposition of organic matter might be responsible for reducing soil pH and inducing the dissolution of fixed nutrients in available forms.…”
Section: Correlation (R) Of Various Soil Parameters With Microbial Countsupporting
confidence: 63%
See 1 more Smart Citation
“…The pH and EC of soil were reported to be negatively affected by the microbial population of jeevamrut and soil. The experimental findings confirm that the application of jeevamrut and biofertilizers have increase the humification and mineralization of organic matter present in the soil to release the nutrients [12,16]. Further, the acidic medium developed during the decomposition of organic matter might be responsible for reducing soil pH and inducing the dissolution of fixed nutrients in available forms.…”
Section: Correlation (R) Of Various Soil Parameters With Microbial Countsupporting
confidence: 63%
“…Biofertilizers, consortia of living microorganisms, have the ability to dissolve the fixed and unavailable nutrients for making them available to the plants [15,16]. Azotobacter is a free-living bacterium that promotes nitrogen sequestration from atmosphere, synthesizes plant growth promoters such as auxin, cytokinin, and gibberellin, and stimulates microbial activities in rhizosphere to enhance the uptake of nutrients by plants [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors summarized that, thanks to the implementation of the PSM with an inoculant carrier, the amount of P-inorganic fertilizer that was required was reduced by 50%. Recently, the same authors [94] studied paddy soil classified as silty clay (46% clay, 41% silt, 13% sand, pH in water-6.47, organic C-1.3%, available P-19 mg kg −1 ). They confirmed that both solid and liquid biofertilizers, which contained the PSM and N-fixing bacteria (e.g., Azosprillum sp., Azotobacter sp.)…”
Section: Discussionmentioning
confidence: 99%
“…Bahan baku amelioran dapat berupa kompos jerami, biochar, dolomit maupun asam humat. Kompos dapat menggemburkan tanah, memperbaiki struktur dan porositas tanah, serta meningkatkan komposisi mikroorganisme tanah, meningkatkan daya ikat tanah terhadap air, menyimpan air tanah lebih lama, dan mencegah lapisan kering pada tanah (Fitriatin et al, 2021). Biochar memiliki kemampuan mengikat air dan pupuk yang cukup tinggi, dan meningkatkan kandungan nitrogen (N) di dalam tanah karena memiliki kapasitas tukar kation (KTK) yang tinggi (Maghdalena et al, 2016).…”
Section: Pendahuluanunclassified